COVID-19 in Pediatrics: Demographic, Clinical, Laboratory, and Radiological Characteristics of Infected Patients With SARS-CoV-2 - Najafinejad, Maryam; Cheraghali, Fatemeh; Aghcheli, Bahman; Rajabi, Abdolhalim; Barati, Leila; Naziri, Hamed; Gharib, Mohammad Hadi; Tabarraei, Alijan; Nakstad, Britt; Tahamtan, Alireza (Frontiers in Pediatrics, 2022)
The COVID-19 disease usually leads to mild infectious disease in children, but some develop serious complications. Here, we describe the characteristics of children with COVID-19 in northern Iran, the Golestan province. Ninety-one confirmed cases were enrolled in the study, aged 0-18 years. Demographic, clinical, comorbidity, laboratory, and radiological data were compared based on the disease severity (admitted to intensive care unit (ICU) or not) and disease outcome (recovered or deceased). Sixteen (17.5%) cases were hospitalized in ICU, and 8/91 (8.8%) deceased. Fever and cough were the most common clinical symptoms. Among all symptoms notified there were no significant differences between severe and milder cases, or between those who deceased and recovered. Failure to thrive (FTT), malignant disease and neurological disease were significantly more prevalent in severe cases as was frequently reported comorbidities. Laterality, ground-glass opacity, and lung consolidation were the most common findings in chest computed tomography. The data confirms that the COVID-19 disease has various presentations in children, and clinical, laboratory, and radiological findings may help predict the development of severe forms of COVID-19 among children.